2019
DOI: 10.1186/s12885-019-5776-0
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a timely diagnosis for teenagers and young adults with cancer: the ACE “too young to get cancer?” study

Abstract: Background Time to diagnosis (TTD) concerns teenagers and young adults (TYA) with cancer and may affect outcome. Methods Healthcare records from 105 TYA in a regional cancer service were assessed to document events from 1st symptom to treatment start. Detailed pathway construction was possible for 104 patients and allowed a multidisciplinary panel review of each pathway with assessment of good practice and lessons for the future. Results 1st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Women and adolescents were more likely to report ‘fear’ as a barrier than men and adults, which has also been found by other studies [ 27 , 53 ]. Adolescents were also found in other studies to express ‘fear’ as an important barrier [ 54 56 ]. A school-based intervention program, aimed at increasing knowledge on cancer signs and symptoms was able to reduce such barriers, at least in the short-term [ 48 ].…”
Section: Discussionsupporting
confidence: 57%
“…Women and adolescents were more likely to report ‘fear’ as a barrier than men and adults, which has also been found by other studies [ 27 , 53 ]. Adolescents were also found in other studies to express ‘fear’ as an important barrier [ 54 56 ]. A school-based intervention program, aimed at increasing knowledge on cancer signs and symptoms was able to reduce such barriers, at least in the short-term [ 48 ].…”
Section: Discussionsupporting
confidence: 57%
“…First, TYAs more commonly seek initial medical advice from primary care prior to a cancer diagnosis 27 and have referral pathways more similar to adult cancer services, such as the 2-week wait referral system. 28 This is in contrast to children with suspected cancer, who are more frequently referred immediately to the emergency department. 29 We also found that the fall in incident diagnoses was specific to certain tumour types, including CNS tumours and lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Like the prolonged periods to diagnosis described in this study, previous research has found that TYAs similarly deal with extended times to diagnosis potentially contributing to unnecessary emergency presentations [36]. Evidence from this study and the paper by Dommett et al [36] suggests that referrals from primary care for suspected cancers in young people should be encouraged and organisational delays, such as errors in referrals, must be reduced for timely investigations.…”
Section: Discussionmentioning
confidence: 51%